In systemic lupus erythematosus anti-dsDNA antibodies can promote thrombosis through direct platelet activation. Issue 107 (February 2020) - Andrianova, Izabella A.; Ponomareva, Anastasiya A.; Mordakhanova, Elmira R.; Le Minh, Giang; Daminova, Amina G.; Nevzorova, Tatiana A.; Rauova, Lubica; Litvinov, Rustem I.; Weisel, John W.
Abstract: Systemic lupus erythematosus (SLE) is associated with a high risk of venous and arterial thrombosis, not necessarily associated with prothrombotic antiphospholipid antibodies (Abs). Alternatively, thrombosis may be due to an increased titer of anti-dsDNA Abs that presumably promote thrombosis via direct platelet activation. Here, we investigated effects of purified anti-dsDNA Abs from the blood of SLE patients, alone or in a complex with dsDNA, on isolated normal human platelets. We showed that anti-dsDNA Abs and anti-dsDNA Ab/dsDNA complexes induced strong platelet activation assessed by enhanced P-selectin expression and dramatic morphological and ultrastructural changes. Electron microscopy revealed a significantly higher percentage of platelets that lost their discoid shape, formed multiple filopodia and had a shrunken body when treated with anti-dsDNA Abs or anti-dsDNA Ab/dsDNA complexes compared with control samples. In addition, these platelets activated with anti-dsDNA Ab/dsDNA complexes typically contained a reduced number of secretory α-granules that grouped in the middle and often merged into a solid electron dense area. Many activated platelets released plasma membrane-derived microvesicles and/or fell apart into subcellular cytoplasmic fragments. Confocal microscopy revealed that platelets treated with anti-dsDNA Ab/dsDNA complex had a heterogeneous distribution of septin2 compared with the homogeneous distribution in control platelets. Structural perturbations were concomitant with mitochondrial depolarization and a decreased content of platelet ATP, indicating energetic exhaustion. Most of the biochemical and morphological changes in platelets induced by anti-dsDNA Abs and anti-dsDNA Ab/dsDNA complexes were prevented by pre-treatment with a monoclonal mAb against FcγRIIA. The aggregate of data indicates that anti-dsDNA Abs alone or in a complex with dsDNA strongly affect platelets via the FcγRIIA receptor. The immune activation of platelets with antinuclear Abs may comprise a prothrombotic mechanism underlying a high risk of thrombotic complications in patients with SLE. Highlights: Anti-dsDNA Abs from the blood of SLE patients activate platelets trough FcγRIIA. Anti-dsDNA-Abs induce platelet degranulation and P-selectin expression. Immune platelet activation includes rearrangement of cytoskeletal proteins. Anti-dsDNA-Abs cause platelet microvesiculation and cytoplasmic disintegration. Immune platelet activation is a prothrombotic mechanism in SLE.